Comparative Study of Commercial and Plastic Waste Resins for Groundwater Treatment - Muhamad, Mimi Suliza; Nur Naqiyah Yunus; Norshuhaila Mohamed Sunar; Noorul Hudai Abdullah; Mohd Farhan Mohd Mukelas (Journal of Advanced Industrial Technology and Application, 2025)
Groundwater contamination by organic and inorganic pollutants poses serious health and environmental concerns. Conventional resins are effective but costly. There is a need for low-cost, eco-friendly alternatives, particularly through plastic waste valorization. This study compares the performance of commercial and plastic waste resins for groundwater treatment. Scanning electron microscopy analysis revealed that the commercial resin had a smooth, porous structure, while the plastic waste resin showed a rough, irregular surface.  Energy dispersive X-ray and Fourier transform infrared spectroscopy analysis confirmed key ion exchange functional groups, including sulfonic acid, in the commercial resin. X-ray diffraction analysis showed the commercial resin was amorphous with low crystallinity. Results showed that the commercial resin outperformed the plastic waste resin by removing 98.6% biochemical oxygen demand (BOD), 85% chemical oxygen demand (COD), 88.9% total suspended solids (TSS), 50% total dissolved solids (TDS), and 66% iron. The plastic waste resin achieved lower removal rates of 66.7% TSS, 25% TDS, and 19.2% COD. In column method, the commercial resin removed 91.65% total hardness within 4 hours at 2163 cm³ dosage, while the plastic waste resin achieved up to 52.12%. The superior performance is linked to the commercial resin’s favorable structure and functional groups for ion exchange.  The use of plastic waste resin as a potential ion exchange material for water treatment supports waste valorization and aligns with circular economy principles. However, its performance requires further optimization, which can be pursued through strategic collaboration with water treatment industries.